Copyright Protection Against the Act of Covering Songs on Youtube Channels in the Regulation of Intellectual Property Rights in Indonesia - Moh. Fadlan Wahidji (Estudiante Law Journal, 2022)
This study aims to determine and describe the form of copyright protection against the act of covering songs on YouTube channels in the regulation of intellectual property rights in Indonesia. The research method used is normative juridical by examining through literature studies. The results of the research based on Article 5 and Article 9 of Law Number 28 of 2014 concerning Copyright, the creator gets legal protection related to songs uploaded by other parties through Youtube which applies anywhere regardless of the media used to announce a song. In addition, songwriters get legal protection from Youtube, namely Youtube will delete videos that violate copyright, but this is only implemented by Youtube if it has received notification of copyright infringement. The legal consequences for Youtube that continues to broadcast songs uploaded without the creator's permission is the closure of the Youtube site as a whole.